2020
DOI: 10.1111/cen.14371
|View full text |Cite
|
Sign up to set email alerts
|

A relook at the 8th edition of the AJCC TNM staging system of anaplastic thyroid carcinoma: A SEER‐based study

Abstract: Objective In the 8th edition American Joint Committee on Cancer (AJCC) tumour‐node‐metastasis (TNM) staging system (TNM‐8), changes have been made regarding anaplastic thyroid carcinoma (ATC) compared with the 7th edition (TNM‐7). The major changes are that anaplastic ATC now has the same T stage definitions as differentiated thyroid cancer, and new staging of IVA and IVB is implemented. However, the clinical impact of the new edition for ATC remains unclear due to scarce and conflicting data. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The same case involves different histological subtypes of thyroid cancer, so we can further study the clinicopathological characteristics of different STC by classifying these subtype combinations. The results showed that the age of SDDTC was younger than that of SMDTC and SADTC, and the average age at diagnosis of SADTC was the largest, followed by SMDTCr, which was similar to the age analysis results of singleton thyroid cancer [31][32][33] .There was no statistically significant gender difference among the three groups,SADTC not only has a longer maximum tumor diameter than SDDTC and SMDTC, but also has a significantly longer disease duration than SDDTC and SMDTC, previously reported that anaplastic carcinoma is highly aggressive, progresses rapidly, and the neck mass expands rapidly [34] .However, the SADTC in our case has a longer course of disease, up to 20 years. There are existing reports on SADTC and the course of the disease are also more than 20 years [9,12] , may be due to undifferentiated progression from differentiated [35] .…”
Section: Discussionsupporting
confidence: 77%
“…The same case involves different histological subtypes of thyroid cancer, so we can further study the clinicopathological characteristics of different STC by classifying these subtype combinations. The results showed that the age of SDDTC was younger than that of SMDTC and SADTC, and the average age at diagnosis of SADTC was the largest, followed by SMDTCr, which was similar to the age analysis results of singleton thyroid cancer [31][32][33] .There was no statistically significant gender difference among the three groups,SADTC not only has a longer maximum tumor diameter than SDDTC and SMDTC, but also has a significantly longer disease duration than SDDTC and SMDTC, previously reported that anaplastic carcinoma is highly aggressive, progresses rapidly, and the neck mass expands rapidly [34] .However, the SADTC in our case has a longer course of disease, up to 20 years. There are existing reports on SADTC and the course of the disease are also more than 20 years [9,12] , may be due to undifferentiated progression from differentiated [35] .…”
Section: Discussionsupporting
confidence: 77%
“…All patients with ATC are stage IV by definition irrespective of disease extent. Intrathyroidal disease is staged as IVA, extrathyroidal or locoregional disease is staged as IVB, while metastatic disease is staged as IVC 7 . According to the 2021 American Thyroid Association (ATA) guidelines for management of patients with ATC, those with stage IVA and ‘resectable’ stage IVB disease should be offered upfront surgical resection 8 .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Given the lack of clarity in the literature regarding what resections have been attempted and what extent of disease patients have preoperatively, especially in stage IVB disease, it…”
mentioning
confidence: 99%
“…Anaplastic thyroid carcinoma (ATC) is an uncommon but profoundly aggressive thyroid malignancy established in undifferentiated follicular thyroid cells [ 1 , 2 ]. It accounts for more than 50% of all deaths attributable to thyroid tumours, with a mean survival period of three to four months and disease-specific mortality at one year of about 100% [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anaplastic thyroid carcinoma (ATC) is an uncommon but profoundly aggressive thyroid malignancy established in undifferentiated follicular thyroid cells [1,2]. It accounts for more than 50% of all deaths attributable to thyroid tumours, with a mean survival period of three to noteworthy nearby compressive symptoms due to a quickly advancing central neck mass (77%), accompanying dysphagia (40%), hoarseness (40%), and stridor (24%).…”
Section: Introductionmentioning
confidence: 99%